Peran Negara Dalam Pengembangan Sistem Ekonomi Kerakyatan menurut UUD 1945 - Zainal Arifin Hosein (Jurnal Hukum IUS QUIA IUSTUM, 2016)
The concept of people economy cannot be separated with the concept of people's welfare. Both concepts, explicitly and implicitly, are contained in Article 33 of the 1945 Constitution. Referring to Article 33 of the 1945 Constitution, it is clear that the national economic system Indonesia is intended for social welfare. The problem in this research is how legal policy able to clarify the people's economic as intended in the principles of Article 33 UUD 1945? By using qualitative research method with normative-juridical approach, the study was emphasized by analyzing a variety of resources related to the issues discussed in this paper. The research concludes that the policy of people economic development becomes essential and a priority in order to realize the people prosperity. This can be achieved if the policy of people economic development is supported by the law in the form of legislation which is able to develop micro, small and medium-scale enterprises to take a part in the national business world.